Tariqa in Indonesia: Social Integration of Religious Adherents - Torik, Muhammad; Asmara, Muhammad Abdillah; Febriani, Fenti (Al-Albab, 2023)
This paper seeks to shed light on how tariqas [school or order of Sufism] play an important role in the socio-religious life of Indonesian society. Furthermore, this paper intends to explore research gaps from previous research by looking at how conflict and social integration among tariqas are in the reality of religious communities. In addition, this paper also aims to explain the causative and supporting factors originating from the tariqa structural institutions and the tariqa interests in social integration among the tariqa. Based on the collected data which were analyzed using a qualitative approach, this article found that the tariqas have become the main agent in maintaining social integration among the tariqa practitioners and minimizing the gaps of conflict between the existing tariqas. However, at the same time, a tariqa needs legitimacy from its followers so that it creates space for conflicts of interest among the tariqa practitioners, especially in the fields of economics, politics, as well as among their followers. This paper is based on research conducted using in-depth library research aimed to find out how conflict and social integration occur in society.